The economic and social impact of teleworking in Romania: Present practices and post pandemic developments - Syed Abdul Rehman Khan; Danish Iqbal Godil; Munaza Bibi; Yu Zhang; Syed Muhammad Ahsan Rizvi (Amfiteatru Economic Journal, 2021)
The emergence of COVID-19 has drastically transformed the way people are working along with that the productivity of firms is also affected due to this catastrophic event that happened at the end of the year 2019. The teleworking aspect has gained momentum during COVID-19 and it has been used extensively by the firms to maintain their operations. This study aims to examine the impact of COVID-19 policies, adoption of advanced technology, and teleworking on firm productivity in Romania with a sample of 328 including the Vice President, Operation Manager, General manager, Logistics Manager, Procurement Manager, and Information system manager while the collected data was analyzed using the CB SEM technique. After analyzing the collected data, we have found that the COVID-19 pandemic plays an imperative role in increasing teleworking practices in Romania, while the COVID-19 pandemic is not viewed as a significant factor in the adoption of advanced technology in Romania. On the other side, this pandemic negatively affects Romania's firm productivity, whereas teleworking and the adoption of advanced technology positively affect the Romanian firms' productivity. Lastly, the adoption of advanced technology helps in increasing the pattern of teleworking in Romania. The increased use of teleworking practices has been regarded as an important practice in Romania to follow the COVID-19 policies imposed by the government on one side, yet to keep the business operation in the smooth run by working from home through employing the technology to maintain the firm productivity.
Keywords: E10; F14; M10; M21; 330; Teleworking; COVID-19; Firms Productivity; Smart technologies